Analysis and design of class E isolated DC/DC converter using class E low dv - Boonyaroonate, I.
A class E isolated DC/DC power converter for regulating the output voltage at a fixed switching frequency is presented, analyzed and experimentally verified. It consists of class E series-resonant inverter, high-frequency transformer and class E low dv/dt pulse width modulation (PWM) synchronous rectifier. By controlling the conduction time of the controlled switch in the rectifier, high-frequency AC current is rectified and the output voltage can be controlled at the same time. The zero voltage switching (ZVS) condition of all switches can be maintained from full-loaded to open-loaded. The theoretical predictions were in good agreement with the experimental measurements and the maximum efficiency measured at a switching frequency of 1 MHz was 91.2%
Keywords: 1 MHz; 91.2 percent; ZVS; Class E isolated DC/DC power converter; Class E low dv/dt PWM synchronous rectifier; Class E series-resonant inverter; Conduction time; High-frequency transformer; Output voltage regulation; Switching frequency; Zero voltage switching